The Potential of Avocado Oil for Topical Use: A Narrative Review - Ratna Hapsari Tri Mustika Dewi; Niswatus Sholihah; Rima Nofitasari; Dhimas Adhityasmara; Ayu Shabrina (Universitas Wahid Hasyim Semarang, 2024)
Skin aging is a multifaceted biological process that is impacted by both internal (genetics, hormones, cellular metabolism, and metabolic processes) and external (long-term exposure to UV light, pollution, ionizing radiation, chemicals, and toxins) aspects. Monounsaturated fatty acids, especially oleic acid, found in avocado oil are beneficial for wound healing, moisturizing, and anti-aging. Finding avocado oil's role as an active ingredient in cosmeceuticals was the aim of this investigation. The study's article review technique entails a thorough search of the Pubmed, Google Scholar, Proquest, Springer Link, and Science Direct databases for articles published between 2018 and 2024. The sample utilized in this study consisted of research publications that satisfied the inclusion criteria, resulting in a total of 12 articles. The result of this study showed that avocado oil is mostly formulated in emulgel and cream preparation. Avocado oil can be used as sunscreen due to the presence of the unsaturated fatty acid such as oleic acid and linoleic acid. All of the topical application of avocado oil showed the potential of this oil as antioxidant, anti-aging and sunscreen. Avocado oil is potential as cosmeceutical at the concentration of 3% to 20%.